Gender-Related Indicators of Well-Being - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2004)
This paper discusses the rationale as well as the challenges involved when constructing gender-related indicators of well-being. It argues that such indicators are critically important but that their construction involved a number of conceptual and measurement problems. Among the conceptual issues to be considered are the space in which gender inequality in well-being is to be measured, whether the indicators should track well being of males and females separately or adjust overall measures of well-being by the gender inequality in well-being, whether gender equality in every indicator is necessarily the goal, how to assess gender inequality that is apparently desired by males and females, and what role indicators of agency or empowerment should play in gender-related indicators of well-being. Among the most important measurement issues to be addressed are the role of the household in allocating resources, the question of stocks versus flows, as well as significant data gaps when it comes to gender inequalities. Where appropriate, remedies to the conceptual and measurement issues are proposed. The paper also briefly reviews UNDP?s gender-related indices to illustrate some of the challenges involved.
Keywords: 330; Einkommensverteilung; Armut; Geschlecht; Sozialer Indikator; Welt